Beyond the Ladder of Participation: An Analytical Toolkit for the Critical Analysis of Participatory Media Processes - Carpentier, Nico (Javnost-The Public, 2016)
Participatory research is facing three challenges—how to deal with the theoretisation and conceptualisation of participation; how to support the research with analytical models; and how the evaluate the research outcomes. This article aims to address these three problems by distinguishing two main approaches (a sociological and a political) in participatory theory and developing a four-level and 12-step analytical model that functions within the political approach. In this analytical model, a series of key concepts are used: process, field, actor, decision-making moment and power. The normative-evaluative problem is addressed by reverting to the critical perspective to evaluate the societal desirability of particular participatory intensities. This critical perspective—potentially—adds a 13th and final normative layer to the analytical model.